Financial and Business Risk: Private IPP, Case on Baturaja Coal Fired SPP 2x25 MW - Marnalom, Marnalom; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2013)
In line with demand of social economic and industry growth in Indonesia, energy development such as electricity infrastructure is a key factor to support. In other hand, shortage of electricity supply in almost whole areas in Indonesia which is increasing 7% a year on the average. In response to this issue, Government instructed PLN under the coal based steam power plant accelerated development program with the total capacity 10.000 MW that consist of PLNÃ¢â‚¬â„¢s power plant development and also Independent Power Producer (IPP) developer. This program is actually purpose to decrease the cost of energy production (Fuel), primary energy diversification program, and to anticipate the delay of investment at private sector. It is necessary to balance the private sectors which build electric power plants and transmit its energy to PLN system through an electric sale agreement scheme called Ã¢â‚¬ËœPPAÃ¢â‚¬â„¢ (power purchase agreement).Ã‚Â By giving opportunity to private investor in charge, PLN is not only expected to provide electricity supply immediately to social and industry, but also getting help for project financing. IPP is developer that builds, operates and maintains the generating units, and sells its electricity to PLN under PPA (power purchase agreement). And one of IPPs in Indonesia is PT.Astratel Nusantara, that proposed development of Baturaja Coal Fired Steam Power Plant 2x25 MW (net) where the plant will be located in regency of Baturaja, South Sumatra. This area is very poor for quality of electricity services from PLN; this includes the service for PLNÃ¢â‚¬â„¢s big customer in industry like PT. Semen Baturaja, both for cement manufacturing process and for housing colony utilization. This final paper will try to evaluate the related aspects to find the answers whether IPP Baturaja 2x25 MW is executable or not by the firmÃ¢â‚¬â„¢s decision makers, by performing a project financial analysis as capital budgeting techniques to help determine the relevant cash flows associated with proposed capital expenditures. Besides that, it is how the project sponsor can mitigate the potential risks by performing project management methodology (PMBOK). Ã‚Â Keywords: capital budgeting Techniques, project risk management, IPP (independent power producer)